Ferromagnetic Insulators: Room‐Temperature Ferromagnetic Insulating State in Cation‐Ordered Double‐Perovskite Sr2Fe1+xRe1−xO6Films (Adv. Mater. 4/2019). Issue 4 (22nd January 2019) - Sohn, Changhee; Skoropata, Elizabeth; Choi, Yongseong; Gao, Xiang; Rastogi, Ankur; Huon, Amanda; McGuire, Michael A.; Nuckols, Lauren; Zhang, Yanwen; Freeland, John W.; Haskel, Daniel; Lee, Ho Nyung
Abstract : A hidden ferromagnetic insulating state with a high Curie temperature is found by Ho Nyung Lee and co‐workers in epitaxial 3d–5d double perovskite films, as described in article number1805389 . Such an intriguing state is rare in nature but critical for realizing quantum electronic and computing devices without dissipating electric power. The front cover image illustrates the spin and orbital structures of Sr2 FeReO6, composed of localized 3d orbitals (red) and spin–orbit‐coupled 5d orbitals (blue).